A study on the effectiveness of advertising, personal selling and sale promotion on promotional activities of Hotel Pontian / Amirah Mohsin - Mohsin, Amirah (Faculty of Business Management, 2011)
Marketing is an element that very important to ensure the successful of an institution. To make sure the activities of marketing success so the marketers have to use the suitable promotional activities. They have five types of promotional tools such as advertising, personal selling; sell promotional, direct marketing and public relation. All this activities will help the Hotel Pontian make sure customer know about organization and help organization expand their business. This study conducted focusing on the “The Effectiveness of Advertising, Personal Selling and Sales Promotion on Promotional Activities of Hotel Pontian”. The main objectives of this study are (1) To determine the level of the effective of advertising, sales promotional and personal selling toward Hotel Pontian customer (2) To identify whether these promotional activities can create or develop brand awareness (3) To analyze and identify alternative that can be used to improve the effective promotional activities to encourage repeat purchase and make sure customer be loyal to Hotel Pontian. From this study I expected that from the promotional activities is important to organization. This study, provide more information to Hotel Pontian and they can use the researcher finding to improve their promotional activities.